A study protocol for a randomized controlled trial to assess the effects of Baduanjin exercise on balance impairment in patients with cervical dystonia - Fan, Shun; Wang, Jixuan; Zhang, Shiying; Tao, Chuanfeng; Huang, Qiao; Jin, Yinghui; Li, Huanan; Wang, Jingui (Frontiers in Neurology, 2025)
BackgroundPatients with cervical dystonia (CD) commonly exhibit varying degrees of impaired balance, abnormal gait, and increased fear of falling. However, Botulinum toxin—the standard of care—does not substantially improve balance or gait. Baduanjin, a traditional Chinese exercise, improves balance in several neurological disorders, yet its effects in CD remain unknown. This protocol describes a randomized controlled trial evaluating the effects of Baduanjin exercise on balance impairment in patients with CD.MethodsThis prospective randomized controlled trial enrolls CD patients with impaired balance. Eligible participants are randomly allocated (1:1) to either a Baduanjin intervention group or a control group without Baduanjin. The Baduanjin group undergoes a 20-week training program. The primary outcome is balance function, evaluated through the Berg Balance Scale. Secondary outcomes include standing static balance ability assessed by the Zebris Stance Analysis FDM System, fall risk conducted using the Timed Up & Go test, gait-related data assessed by the Zebris Gait Analysis FDM System, the severity of CD assessed by the Toronto Western Spasm Rating Scale, and the anxiety status of patients assessed by the Hamilton Anxiety Rating Scale. The entirety of the data are collected at the baseline, 2, 6, 12, and 20 weeks. A two-way mixed analysis of variance (ANOVA) or generalized estimating equations are used to assess the effectiveness of Baduanjin.DiscussionThis protocol is the first randomized controlled design to evaluate Baduanjin for balance and gait in cervical dystonia, combining objective instrumented outcomes with validated clinical scales and a pragmatic supervised-to-home regimen, thereby providing decision-relevant evidence.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/zh-CN/Home/ProjectView?pid=fce76993-0978-484e-ba50-c097b35805c7, ITMCTR2024000240.